Computability on Quasi-Polish Spaces - Hoyrup, Mathieu; Rojas, Cristóbal; Selivanov, Victor; Stull, Donald M. (Descriptional Complexity of Formal Systems, 2019)
We investigate the effectivizations of several equivalent definitions of quasi-Polish spaces and study which characterizations hold effectively. Being a computable effectively open image of the Baire space is a robust notion that admits several characterizations. We show that some natural effectivizations of quasi-metric spaces are strictly stronger.